2014
DOI: 10.15376/biores.9.4.6041-6072
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of an Organosolv Process for Bioethanol Production

Abstract: In a previous paper, conceptual process design, simulation, and mass and energy balances were presented for an organosolv process with a hardwood feed of 2350 metric tons (MT) per day and ethanol, lignin, furfural, and acetic acid production rates of 459, 310, 6.6, and 30.3 MT/day, respectively. In this paper, the investment and operating costs of the process and the minimum ethanol selling price (MESP) to make the process economically feasible were estimated. The total capital investment of the plant was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 33 publications
(87 reference statements)
3
42
2
Order By: Relevance
“…A comprehensive 2013 report by the US National Renewable Energy Laboratory (NREL) concluded that achievement of the target value of 3.00 US dollars per gallon of gasoline equivalent fuel required lignin valorization [242]. Kautto et al modeled the organsolv-based production of ethanol from hardwood with lignin, furfural, and acetic acid as co-products [243]. Consistent with the NREL conclusion, the value of the lignin product was a strong determinant of the minimum ethanol selling price.…”
Section: Economic Analysis Of Lignin Utilization Strategiesmentioning
confidence: 95%
“…A comprehensive 2013 report by the US National Renewable Energy Laboratory (NREL) concluded that achievement of the target value of 3.00 US dollars per gallon of gasoline equivalent fuel required lignin valorization [242]. Kautto et al modeled the organsolv-based production of ethanol from hardwood with lignin, furfural, and acetic acid as co-products [243]. Consistent with the NREL conclusion, the value of the lignin product was a strong determinant of the minimum ethanol selling price.…”
Section: Economic Analysis Of Lignin Utilization Strategiesmentioning
confidence: 95%
“…As demonstrated, ethanol-focussed biorefineries involve a pre-treatment step, aimed at improving the sugar hydrolysis and fermentation yields which normally involves a physical, chemical or biological process, or a combination of these [9]. Pre-treatment for ethanol or fuel production often damages other components in the biomass and as lignin is not used for the ethanol production, it's value is limited to fuel for electricity to reuse in the ethanol production process [10,11] or as a local heat source [12]. However, alternate, multi-product biorefinery technology configuration options are now considered to make use of the whole lignocellulosic feedstock for chemicals and value added products, utilising the three core polymers in the feedstock, namely, cellulose, hemicellulose and lignin [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, a selection of pre-treatment solvents have been considered in techno-economic analyses i.e. ionic liquid treatment [16], organosolv treatments [12,17,18] and acid pre-treatment [19] which are used for a variety of products such as ethanol, lignin, furfural, cellulose, succinic acid and acetic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, in these cases lignin is recovered and valorised as fuel as a mean to economically sustain the process. A different concept is at the basis of the "Organosolv" process, which dissolves lignin in a proper organic solvent in order to recover it in pure form to be valorised as chemical or additive [3]. Some demonstrative scale processes have been developed and reviewed by Kautto et al [3] with attention to the minimum ethanol selling price resulting from different technologies.…”
mentioning
confidence: 99%
“…A different concept is at the basis of the "Organosolv" process, which dissolves lignin in a proper organic solvent in order to recover it in pure form to be valorised as chemical or additive [3]. Some demonstrative scale processes have been developed and reviewed by Kautto et al [3] with attention to the minimum ethanol selling price resulting from different technologies. Capital costs, annual cash flows and sensitivity analysis towards different parameters (technical and market-related) have been considered.…”
mentioning
confidence: 99%